Discharge Against Medical Advice in Teaching Hospitals: A Telephone Survey - Majid Heydari; Omid Khosravizadeh; Rohollah Kalhor; Marziye Sharifi; Azadeh Ahmadzadeh Ghasab (Iran University of Medical Sciences, 2017)
Background: Discharge with personal consent is considered as one of the main problems in hospitalization condition since many patients leave the hospital prematurely against the doctor's advice. Thus, the aim of this study was to identify the factors affecting the discharge with personal satisfaction in selected teaching hospitals of Tehran University of Medical Sciences. Methods: The present study was a descriptive and cross-sectional analysis that was carried out on patients discharged with personal satisfaction from selected training hospitals of the Tehran University of Medical Sciences in 2016. The sample size was 153 patients who were randomly selected from Sina, Shariati and specialized women hospitals. The data were collected through using a self-made checklist and telephone interview. The SPSS V. 18 software and statistical tests such as Chi-square and t-test were used for data analysis. Results: The most common causes of patient's discharge with personal satisfaction was personal issues related to the sick and the highest among these causes was patient recovery. The least common causes of discharge with personal satisfaction was related to the hospital. There was no significant link of gender, age, place and insurance type with personal discharge, but there was a significant link between the discharges of the hospital with own agreement and type of the hospital (P < 0.05). Conclusion: Hospital staff education, motivating the staff to participate actively in obtaining consent from patients and informing the patients about the stage of their treatment and recovery should be considered as priority management activities.